The impact of vitamin E and/or selenium dietary supplementation on growth parameters and expression levels of the growth-related genes in broilers - Olla A. Khalifa; Rasha A. Al Wakeel; Shabaan A. Hemeda; Mohamed M. Abdel-Daim; Ghadeer M. Albadrani; Ahmad El Askary; Sabreen E. Fadl; Fatma Elgendey (BMC Veterinary Research, 2021)
Abstract Background Broilers are continuously stressed because of the rapid growth rate and the environmental issues associated with industrialized poultry production systems, which lead to higher susceptibility for infection with pathogens. It is well known that vitamin E (Vit. E) and selenium (Se) supplementation have protective functions in such stressful conditions. This protocol was to investigate the impact of Vit. E and/or Se on the production performance, some serum biochemistry, and expression of some growth-related gene in the liver tissue of the broilers. The day-old chicks were allotted into four groups according to the supplement; Control group and groups supplemented with Vit. E and/or Se into Vit. E group (100 mg Vit. E/kg diet), Se group (0.3 mg sodium selenite/kg diet), and Vit E + Se group that supplemented with both Vit. E and Se. Results The data of the present experiment showed that dietary inclusion of Vit. E and/or Se significantly (P ≤ 0.05) improved the production parameters without any side effect on the general health status of the broilers, which indicated by normal serum biochemical parameters. Moreover, the treatments positively affected the expression of some genes related to growth performance including growth hormone receptor (GHR) and insulin-like growth factor 1 (IGF1) in the liver tissue of broilers. Conclusion Dietary supplementation of Vit. E and/or Se improved the production parameters and upregulate the growth-related genes without effect on the general health status of the broilers.